2018
DOI: 10.1097/cmr.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical treatment landscape and economic burden of locoregional and distant recurrence in patients with operable nonmetastatic melanoma

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
18
5
Order By: Relevance
“…In contrast, one study reported a recurrence rate of 19% at a mean follow-up of 23.1 months [20], which was lower than that reported in our study. [20]. The current study highlights the risk of recurrence in patients with resected early-stage melanoma.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, one study reported a recurrence rate of 19% at a mean follow-up of 23.1 months [20], which was lower than that reported in our study. [20]. The current study highlights the risk of recurrence in patients with resected early-stage melanoma.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study reported recurrence in 48% of patients with resected stage IIIA melanoma at 5 years; however, this earlier study used older data (1992–2004) from a single site [ 19 ]. In contrast, one study reported a recurrence rate of 19% at a mean follow-up of 23.1 months [ 20 ], which was lower than that reported in our study. This may have been due to the inclusion of a younger patient population (mean age 53.8 years) with stage I and IIA melanoma who have a lower risk of recurrence [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Costs of monitoring and follow-up in the adjuvant and metastatic settings, and the treatment of LR and DR (excluding the costs of medications) were based on results of a retrospective health insurance claims study of melanoma patients 39 . Based on NCCN guidelines for follow-up and monitoring of patients with melanoma, costs of follow-up in years 3-5 and 6 or more were estimated to be 50% and 25% of those in years 1-2, respectively 40 .…”
Section: Costsmentioning
confidence: 99%